Study of daytime high-altitude discharges using plasma-chemistry model. (15th September 2021) - Evtushenko, Andrey; Kuterin, Fedor; Svechnikova, Ekaterina
Abstract: The paper considers the formation of electric fields in the atmosphere at altitudes of 50–70 km after especially powerful tropospheric cloud-to-ground discharges, leading to the initiation of high-altitude discharges. It is known that a necessary condition for initiation of a nighttime sprite is the electric field of uncompensated charge in a cloud of more than 128 Td at an altitude of about 75–80 km, while the field 80–100 Td leads to the development of a halo. High conductivity in daytime conditions does not allow the electric field to penetrate to altitudes of 75–80 km, and the region of a possible initiation of high-altitude discharges shifts lower. The normalized field required for the discharge initiation is the same as for nighttime conditions. Thus, for the initiation of the atmospheric discharge at daytime several times more intense lightning discharge in the troposphere is needed. Perturbations of the concentrations of ions, neutral compounds, excited atoms and molecules along with disturbances of the atmospheric conductivity and electric field are studied. The uncompensated charge of a parent flash is typically characterized by the impulse charge moment (ICM) of several hundred C ⋅ km for nighttime discharges. Modeling of daytime conditions was carried out in the range of 2000–4000 C ⋅ km, which leads to the formation at an altitude of 50–70 km of a normalized electric field of a near-breakdown value. It is shown that there are two scenarios of development of the discharge, with and without a rapid increase in electron concentration, which are studied in detail by assuming ICM values of 3750 C ⋅ km and 2750 C ⋅ km respectively. During a discharge with an ICM of 2750 C ⋅ km, the decrease in the concentration of electrons in the electric field is caused by their attachment to molecular oxygen, and no sharp increase in electron concentration occurs; the concentrations of the most significant ions and electrons reach unperturbed values in less than a second. The normalized electric field reaches a maximum value of 100 Td, and this scenario corresponds to the development of a halo. For an ICM of 3750 C ⋅ km, an initial decrease in the electron concentration is followed by the formation of an avalanche of electrons characterized by an increase in their concentration by more than an order of magnitude relative to the initial value. The maximum normalized electric field reaches 128 Td, this scenario corresponds to the development of a sprite. Thus, the possibility of the initiation of high-altitude discharges (presumably sprites and halos) in daytime conditions at altitudes of 50–70 km after especially powerful lightning discharges in the troposphere is shown, the dynamics of the disturbance of the chemical balance and atmospheric conductivity is studied. Highlights: A plasmachemical model of a daytime high-altitude discharge is developed. The initiation of daytime discharges requires a powerful lightning discharge. A lightning with the impulse charge moment (ICM) 2750 C ⋅ km initiates a halo. A lightning with the ICM 3750 C ⋅ km leads to discharge similar to sprite.